Astrocytic and microglial interleukin-1β mediates complement C1q-triggered orofacial mechanical allodynia. (March 2023) - Hong, Chaoli; Hayashi, Yoshinori; Hitomi, Suzuro; Kurisu, Ryoko; Urata, Kentaro; Shibuta, Ikuko; Toyofuku, Akira; Iwata, Koichi; Shinoda, Masamichi
Abstract: Glial cells, such as microglia and astrocytes, in the trigeminal spinal subnucleus caudalis (Vc) are activated after trigeminal nerve injury and interact with Vc neurons to contribute to orofacial neuropathic pain. Complement C1q released from microglia has been reported to activate astrocytes and causes orofacial mechanical allodynia. However, how C1q-induced phenotypic alterations in Vc astrocytes are involved in orofacial pain remains to be elucidated. Intracisternal administration of C1q caused mechanical allodynia in the whisker pad skin and concurrent significant upregulation of glial fibrillary acidic protein and ionized calcium-binding adapter molecule 1 in the Vc. Immunohistochemical analyses clarified that C1q induces a significant increase in the cytokine interleukin (IL)-1β, predominantly in Vc astrocytes and partially in Vc microglia. The number of c-Fos-positive neurons in the Vc increased significantly in response to C1q. IL-1 receptor antagonist (IL-1Ra) was used to analyze the involvement of IL-1β in C1q-induced mechanical allodynia. Intracisternal administration of IL-1Ra ameliorated C1q-induced orofacial mechanical allodynia. The present findings suggest that IL-1β released from activated astrocytes and microglia in the Vc mediates C1q-induced orofacial pain. Highlights: Complement C1q triggers orofacial mechanical allodynia and concurrent activation of astrocytes and microglia in the Vc. Activated astrocytes and microglia produce proinflammatory cytokine interleukin-1β. Inhibiting the interleukin-1β pathway ameliorates C1q-induced orofacial mechanical allodynia.